Culprit vessel revascularization first with primary use of a dedicated transradial guiding catheter to reduce door to balloon time in primary percutaneous coronary intervention - Guo, Jincheng; Wang, Guozhong; Li, Zixuan; Liu, Zijing; Wang, Yujie; Wang, Senhu; Wang, Yuntao; Wu, Yongxia; Wang, Haotian; Wang, Yuping; Zhang, Libin; Hua, Qi (Frontiers in Cardiovascular Medicine, 2022)
Background The effect of a single transradial guiding catheter (STGC) for culprit vessel percutaneous coronary intervention (PCI) first on door-to-balloon (D2B) time remains unclear. Materials and methods Between February 2017 and July 2019, 560 patients with ST-elevation myocardial infarction (STEMI) were randomized into either the STGC group (n = 280) or the control group (n = 280) according to direct culprit vessel PCI with a STGC. In the STGC group, a dedicated transraidal guiding catheter (6F either MAC3.5 or JL3.5) was used for the treatment of electrocardiogram (ECG)-guided culprit vessel first and later contralateral angiography. In the control group, a universal diagnostic catheter (5F Tiger II) was used for complete coronary angiography, followed by guiding catheter selection for culprit vessel PCI. The primary endpoint was D2B time, and the secondary endpoint included catheterization laboratory door-to-balloon (C2B), procedural, fluoroscopy times, and major adverse cardiac events (MACE) at 30 days. Results The median D2B time was significantly shorter in the STGC group compared to the control group (53.9 vs. 58.4 min; p = 0.003). The C2B, procedural, and fluoroscopy times were also shorter in the STGC group (C2B: 17.3 vs. 24.5 min, p < 0.001; procedural: 45.2 vs. 49.0 min, p = 0.012; and fluoroscopy: 9.7 vs. 11.3 min, p = 0.025). More patients achieved the goal of D2B time within 90 min (93.9% vs. 87.1%, p = 0.006) and 60 min (61.4% vs. 51.1%, p = 0.013) in the STGC group. Radial artery perforation (RAP) was significantly reduced in the STGC group compared with the control group (0.7% vs. 3.2%, P = 0.033). MACE at 30 days was similar (2.5% vs. 4.6%, P = 0.172) between the two groups. Conclusion ECG-guided immediate intervention on culprit vessel with a STGC can reduce D2B, C2B, procedural, and fluoroscopy times (ECG-guided Immediate Primary PCI for Culprit Vessel to Reduce Door to Device Time; NCT03272451).